Expression of the human or porcine C-type lectins DC-SIGN/L-SIGN confers susceptibility to porcine epidemic diarrhea virus entry and infection in otherwise refractory cell lines. (August 2021) - Zhao, Pengwei; Xu, Ling-Dong; Zhang, Yating; Cao, Hongwei; Chen, Ruiai; Wang, Bin; Huang, Yao-Wei
Abstract: Porcine epidemic diarrhea virus (PEDV) is an alphacoronavirus that causes great economic losses in the porcine industry. Although the functional receptor for the virus has not been identified, multiple isolates are able to infect different cell lines. Recently, it has been shown that the human C-type lectin DC-SIGN/L-SIGN (hDC-SIGN/L-SIGN) can promote entry of several coronaviruses. Here we examined whether hDC-SIGN/L-SIGN and its porcine homolog (pDC-SIGN) are entry determinants for PEDV. Expression of hDC-SIGN/L-SIGN or pDC-SIGN in refractory cells dramatically increased infection by a recombinant PEDV expressing green fluorescent protein. In both cases, lectin-mediated infection was inhibited by mannan or anti-hDC-SIGN/L-SIGN or pDC-SIGN antibodies; however, d -galactose had no effect on the virus-infected cells. Our results demonstrate that hDC-SIGN/L-SIGN or pDC-SIGN can mediate the cellular entry and propagation of PEDV, which provides a new theoretical basis for further understanding the infection mechanism of PEDV, and will be helpful for the development of novel therapeutic agents. Highlights: Expression of hDC-SIGN, hL-SIGN or pDC-SIGN in refractory cells confers PEDV entry. PEDV entry of DC-SIGN/L-SIGN-expressing cells leads to replication and propagation. Blockage of C-lectins by mannan or antibodies reduces PEDV infection.